Determining the maturity level of business organizations for ICT implementation in the case of electronic content management - Milenković, Dejan S. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Starting from the fact that the use of electronic content is an imperative of our time, and from a general opinion that the application of modern information technologies can establish a solution for a reliable and simple organization and systematization of documentation, it can be stated that the organization's success depends directly on the achieved level of information management. Timely, accurate, verifiable, readily available and consistent data are more than necessary for business activities; however, the basic problem of the use of these data is not their existence, but the place and manner in which these data are stored and organized within distributed business units. In addition, the introduction of information technologies into  business processes results in more and more useful data; nevertheless, the question is the degree of their utilization. The object of the study was to determine the degree of "maturity" of business organizations for the implementation of information and communication technologies, viewed through the prism of organizational, personnel and technological maturity of an organization for the implementation of an electronic content management system. At the same time, the use of appropriate maturity models for electronic content management aims at approaching the maturity model concept to business organizations.
Keywords: business organizations; maturity models; content management system; electronic content; ICT